Crisis Program Review. (Policy Papers; Policy Paper ;, 2015)
This paper provides an updated review of Fund-supported programs undertaken during the global financial crisis. It follows a series of previous reviews during 2009-12 that assessed program design and outcomes during the surge in Fund supported programs since 2008. The review covers experience during 2008-15 for 32 arrangements financed from the Fund's general resources account (GRA). It covers 27 countries for which arrangements were approved during September 2008-June 2013, with two years or more of program performance.